Cytologic findings from a benign giant cell tumor of the tendon sheath in a dog. (14th April 2014) - Campbell, M. Wesley; Koehler, Jey W.; Weiss, Richard C.; Christopherson, Pete W.
Abstract A 6‐year‐old male neutered Australian Shepherd dog was presented for evaluation of a subcutaneous mass on the plantar aspect of the proximal left metatarsus. Fine‐needle aspirate smears contained numerous plump spindle cells and large multinucleated cells amongst a considerable amount of pink extracellular matrix. Histopathologic diagnosis of the tissue obtained during initial biopsy and eventual surgical cytoreduction of the mass was a benign giant cell tumor of the tendon sheath (GCTTS). Immunohistochemically, the synovioblastic neoplastic cells were diffusely strongly positive for vimentin and S‐100, were multifocally moderately positive for cytokeratin AE1/3, and were negative for CD18, muscle‐specific actin (MSA), and melanoma‐associated antigen (mutated) 1 (MUM‐1). The dog recovered from surgery and underwent definitive radiation therapy to treat the local residual disease. Eight months later, the mass had not recurred. The diagnosis of GCTTS in this case supports previously published reports describing GCTTS as a relevant disease entity in dogs, and provides the first documentation of cytologic findings with this tumor. Further investigation is needed to correlate pathologic features with clinical behavior and response to therapy in dogs.